Asymmetric information and credit rationing in a model of search - Cemil Selcuk (Cardiff University, Cardiff Business School, 2024)
This paper presents a competitive search model focusing on the impact of asymmetric information on credit markets. We show that limited entry by lenders results in endogenous credit rationing, which, in turn, plays a key role in managing adverse selection and prevents the credit market from collapsing.
Keywords: D82; D43; G20; 330; Asymmetric Information; Credit Rationing; Directed Search